Perception towards sex education among UNIMAS community - Nadzirah, Binti Mohd Tahir (Universiti Malaysia Sarawak (UNIMAS), 2013)
With the increased rate of baby dumping cases and other related social problems in Malaysia which is very worrying, there were many debates on how to cope with the problems. One of the solutions proposed by the government was to implement sex education in school. However, this stirs a lot of controversial issues due to differences in opinions and perceptions about the implementation of sex education in schools. This study aimed to examine the perception of UNIMAS community towards sex education and its associate factors which indirectly would influence their perceptions. This study was conducted using quantitative approach whereby a cross sectional study using descriptive design was adopted. A total of 150 respondents were recruited using stratified random sampling whereby the number of samples was calculated based on its actual total popUlation for each stratum which were divided into students, academic staffs and non academic staffs. Data was analysed using descriptive statistics and chi square test. Results showed that 54.7% (n=8l) of respondents had negative perceptions meanwhile 46% (n=69) had positive perceptions toward sex education. Their main source of sex information was peers (68.7%). Types of occupation, molhers' highest educational level, parents as a source of sex information, cultural or religion factors were found to have significant relationships with perception towards sex education. It can be seen that policy makers need to be cognizant on people perception towards sex education if it is to be implemented successfully.